2015
DOI: 10.3324/haematol.2015.131680
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed childhood acute lymphoblastic leukemia in the Nordic countries: prognostic factors, treatment and outcome

Abstract: R elapse is the main reason for treatment failure in childhood acute lymphoblastic leukemia. Despite improvements in the up-front therapy, survival after relapse is still relatively poor, especially for high-risk relapses. The aims of this study were to assess outcomes following acute lymphoblastic leukemia relapse after common initial Nordic Society of Paediatric Haematology and Oncology protocol treatment; to validate currently used risk stratifications, and identify additional prognostic factors for overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 50 publications
(73 reference statements)
8
132
12
1
Order By: Relevance
“…Despite attempts to improve cytotoxic chemotherapy regimens for ALL relapse, the rate of second relapses is high and the overall survival is still relatively poor. In our previous study, we observed an improvement in survival between the relapse periods 1992–2001 and 2002–2011 . This was mainly caused by a decrease in the frequency of second relapses but in this study we did not observe a difference in TRM between the relapse periods.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Despite attempts to improve cytotoxic chemotherapy regimens for ALL relapse, the rate of second relapses is high and the overall survival is still relatively poor. In our previous study, we observed an improvement in survival between the relapse periods 1992–2001 and 2002–2011 . This was mainly caused by a decrease in the frequency of second relapses but in this study we did not observe a difference in TRM between the relapse periods.…”
Section: Discussioncontrasting
confidence: 58%
“…Surprisingly none of the patients with DS died of treatment‐related causes. In our previous study, patients with ALL relapse and DS had a poor overall survival caused by the high occurrence of second relapses . This is in contrast to previous findings where patients with DS‐ALL had worse outcome mainly because of the high incidence of TRM .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It has been suggested that a higher incidence of treatment‐related toxicity could result in dose reduction of some drugs, such as methotrexate. Treatment of relapsed/refractory ALL remains an important challenge in patients with DS because of increased TRM and the high rate of relapse . In this context, enrolling patients with DS‐ALL in clinical trials with immunotherapy is crucial, because the potentially less severe myelosuppression in these therapies could result in less toxicity …”
Section: Discussionmentioning
confidence: 99%